Green Building With Concrete : sustainable design and construction - Sabnis, Gajanan M. (Boca Raton : CRC Press, 2015)
Illustrates the Global Relevance of SustainabilityApplicable to roads, bridges, and other elements of the infrastructure, Green Building with Concrete: Sustainable Design and Construction, Second Edition provides an overview of all available information on the role of concrete in green building. A handbook offering viewpoints from worldwide experts on the global nature of the sustainability movement, it highlights research on economic analysis, in particular the International Organization for Standardization, Environmental Management-Life Cycle Assessment-Principles and Framework application o.
Chapter 10: Sustainability and Rehabilitation of Concrete StructuresChapter 11: Global Sustainability and Concrete; Chapter 12: Sustainable Concrete with Industrial and Postconsumer By-Product Materials; Chapter 13: Sustainability of Steel Reinforcement; Chapter 14: Coatings for Creating Green Infrastructure; Chapter 15: Materials' Specifications : The Missing Link to Sustainability Planning; Back Cover
Includes bibliographical references and index.
Keywords: Concrete construction; Sustainable construction; Concrete -- Recycling